Autoimmunity to bactericidal/permeability-increasing protein in bronchiectasis exhibits a requirement for Pseudomonas aeruginosa IgG response. Issue 2 (7th February 2019) - Skopelja-Gardner, Sladjana; Theprungsirikul, Jomkuan; Meagher, Rachel E.; Beliveau, Cathleen M.; Bradley, Katherine E.; Avery, Meade; Henkle, Emily; Siegel, Sarah; Gifford, Alex H.; Winthrop, Kevin L.; Rigby, William F.C.
In bronchiectasis, due to diseases other than cystic fibrosis, idiopathic, genetic and environmental factors alter the airway landscape and immune responses, rendering the patients susceptible to infection, with the Gram-negative bacterium (GNB) Pseudomonas aeruginosa as a major contributor to mortality [1, 2]. The high prevalence of P. aeruginosa in bronchiectasis patients cannot be explained by a single genetic or environmental influence, and immunological permissiveness of bronchiectasis airways to this colonisation remains unexplained [2]. A similar predisposition to this pathogen is characteristic of cystic fibrosis patients, in whom a single genetic mutation ( CFTR ) shapes the abnormal lung environment. Large subpopulations of patients with bronchiectasis due to diseases other than cystic fibrosis (∼50% in two independent cohorts) develop autoantibodies to BPI, which arise specifically in the context of chronic Pseudomonas aeruginosa infection http://ow.ly/1LHZ30mtfXu